2013
DOI: 10.1063/1.4810073
|View full text |Cite
|
Sign up to set email alerts
|

Surface-based manipulation of point defects in rutile TiO2

Abstract: Role of point defects and HfO2/TiN interface stoichiometry on effective work function modulation in ultra-scaled complementary metal-oxide-semiconductor devices Structure, stability, and mobility of small Pd clusters on the stoichiometric and defective TiO2 (110) surfaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 47 publications
2
67
0
Order By: Relevance
“…Hollister and colleagues found that the spatial profiles of isotope-labelled oxygen absorbed by TiO 2 are decaying exponentials (Supplementary Fig. 6), consistent with the interstitial oxo-species diffusion model 8,9 . We found a remarkably good fit between the temporal profiles predicted by the inward diffusing oxo-species model for all profiles measured (for example, Figs 2, 4 and 5), while the square-root uptake profile predicted by the standard vacancy diffusion model is not capable of a good fit (for example, Fig.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…Hollister and colleagues found that the spatial profiles of isotope-labelled oxygen absorbed by TiO 2 are decaying exponentials (Supplementary Fig. 6), consistent with the interstitial oxo-species diffusion model 8,9 . We found a remarkably good fit between the temporal profiles predicted by the inward diffusing oxo-species model for all profiles measured (for example, Figs 2, 4 and 5), while the square-root uptake profile predicted by the standard vacancy diffusion model is not capable of a good fit (for example, Fig.…”
mentioning
confidence: 59%
“…Materials that depend on this mechanism are useful only at high temperatures, or have a low oxygen uptake capacity that is limited by the sites available for surface absorption or adsorption. However, recent evidence presented by Seebauer and co-workers 8,9 supports a hypothesis that there may also be an interstitial oxygen defect in TiO 2 that can be exceptionally mobile. If it does indeed exist, this new entity could necessitate a revision of more than 50 years of literature on defects in oxides.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Typical activation energies associated with oxygen vacancy diffusion in TiO 2 are of the order 2.6 eV. [51][52][53][54] Even considering the effect of hole trapping which can reduce the activation energy to oxygen vacancy generation, these results suggest that diffusion of pre-existing oxygen vacancies is always much more facile than defect generation in bulk TiO 2 . However, activation energies near the electrode interface [70][71][72] or at grain boundaries 12,73,74 may be considerably lower.…”
Section: Discussionmentioning
confidence: 90%